Communication with the public in the health-care system: a descriptive study of the use of social media in Local Health Authorities and public hospitals in Italy - Marina Vanzetta; Ercole Vellone; Alberto Dal Molin; Gennaro Rocco; Maria Grazia De Marinis; Alvaro Rosaria (Istituto Superiore di Sanità, 2014)
INTRODUCTION. In 2010 the Italian Ministry of Health set out recommendations for the use of social technology and Web 2.0, inviting organisations within the Italian national health service (Servizio Sanitario Nazionale, SSN) to equip themselves with instruments. Objectives. 1. to ascertain how many local health authorities (Aziende Sanitarie Locali, ASL) and public hospitals have a presence on the most widely used social media websites in Italy: Facebook, Twitter and YouTube; 2. to find out how well the Facebook, Twitter and YouTube pages of ASLs and public hospitals are known among the general population; 3. to find out how ASLs and public hospitals engage with the general public on social media sites. MATERIALS AND METHODS. The websites of all ASLs and public hospitals across the country were visited to look for the icons of the social media sites under examination. The data considered were publicly available upon access. RESULTS. A total of 245 websites were analysed. 7.34% ASLs and hospitals had social media accounts. 8 organisations had an account on all three of the social media sites considered in the study. CONCLUSIONS. The results show a low presence of ASLs and hospitals on social media. Other studies are needed in this field.